Saúde bucal de adolescentes que receberam assistência odontológica na primeira década de vida - Amaral, Jaqueline Canova Paludetto [UNESP] (2015)
This study conducted a clinical evaluation whose purpose was to investigate the oral health status of adolescents who participated in an educational and preventive dental program. This program is divided into two phases, the first of which comprises the child's care from the first year of life until they are 4 years old and in the second phase, dental care are kept in the Preventive Clinic up to 9 years old. The sample included 201 teenagers, 56% female and 44% male, who underwent a dental exam to assess oral health status. The dental exam consisted of an assessment of dental caries prevalence and radiographic bitewing examination interproximal, gingival health by community periodontal index; dental occlusion by dental aesthetics index and dental fluorosis occurrence (WHO index). The participants DMFT index was 1.18. Regarding gingival condition, 86% of the sample presented healthy gum tissue. In orthodontic evaluation, 198 patients (98,50%) presented maxillary overjet, one patient (0.5%) had mandibular overjet and 2 patients (1.0%) had anterior open bite. It was also observed that 92% of adolescents did not have dental fluorosis. It can be concluded that patients participating in this study exhibited indexes that reflect, a great state of oral health